Analisis Konsumsi Masyarakat Indonesia Sebelum dan Setelah Krisis Ekonomi - Fikri, Muhammad; Amir, Amri; Achmad, Erni (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2014)
This study aims to determine and analyze how big the marginal propensity to consume (MPC) and the average propensity to consume (APC) the people of Indonesia before and after the economic crisis and to find out and analyze what factors are affecting the consumption of Indonesian society. The method used in this research is descriptive and quantitative methods. From the research : 1) the marginal propensity to consume (MPC) the people of Indonesia after the economic crisis has decreased and the average propensity to consume (APC) the people of Indonesia after the economic crisis have increased.Â Â 2) Before the economic crisis affecting consume of Indonesian society is the national income and deposit rates. After the economic crisis affecting consume of Indonesian society is the national income and inflation. And overall, both before and after the economic crisis affecting consume of Indonesian society is the national income and deposit rates. Keywords: Marginal Propensity to Consume, Average Propensity to Consume, Economic Crisis